2020
DOI: 10.1142/s0219525920500228
|View full text |Cite
|
Sign up to set email alerts
|

Simplicity From Complexity: On the Simple Amplitude Dynamics Underlying Covid-19 Outbreaks in China

Abstract: COVID-19 confronts societies and individuals with unprecedented challenges. It is advocated that complex systems theory, in general, and synergetics, in particular, provide a valuable and comprehensive repertoire of tools and concepts such as the concept of amplitude equations and order parameters to study the spread of COVID-19 in human populations. Specifically, within the framework of SIR and SEIR compartment models COVID-19 trajectories are described in terms of amplitude equations and order parameters. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The benefits of this approach has been demonstrated in previous works. Pervious works on the epidemiological level have suggested that COVID-19 outbreaks in populations evolve along unstable eigenvectors [8,[49][50][51][52][53]. Figure 1 (panels (a) and (b)) shows results that illustrate this point and have been obtained in earlier studies by Pang et al [7] and Frank [8,50].…”
Section: Introductionsupporting
confidence: 70%
“…The benefits of this approach has been demonstrated in previous works. Pervious works on the epidemiological level have suggested that COVID-19 outbreaks in populations evolve along unstable eigenvectors [8,[49][50][51][52][53]. Figure 1 (panels (a) and (b)) shows results that illustrate this point and have been obtained in earlier studies by Pang et al [7] and Frank [8,50].…”
Section: Introductionsupporting
confidence: 70%
“…The eigenvectors of read The perturbation involves . The amplitude equations can be found in previous studies [ 12 , 13 , 15 ] and read with where | M | denotes the determinant of the eigenvector matrix: and . The dynamics of the non-infected system is given by Furthermore, the mappings and read explicitly and The amplitude space description of the SEIR model will be used below to show how to describe stages of COVID-19 epidemics in amplitude space.…”
Section: Infected Subsystems: An Amplitude Space Perspectivementioning
confidence: 99%
“…The perturbation u = X − X st = (E, I, u 3 , R) involves u 3 = S − N ≤ 0. The amplitude equations can be found in previous studies [12,13,15] and read…”
Section: Sir and Seir Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been studied extensively also in the realm of statistical physics of disordered systems (e.g., [17][18][19]). More recently, a great deal of interest has been devoted to the study and development of new scenarios to describe COVID-19 spreading [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In addition, we can mention that a lot of attention has been drawn to population structures displaying complex and heterogeneous connectivity patterns, as well as to the associated dynamics of epidemic and infection spreading processes in the so-called metapopulation models [36,37].…”
Section: Introductionmentioning
confidence: 99%